THE TRANSFORMATION OF TRADITIONAL FOLKLORE INTO ANIMATION: IMPACT ON TODAY’S SOCIETY - Lee J. C., Lee; A. S. Shminan, Shminan; S. Bujang, Bujang; M. Aren, Aren (2021)
Abstract As most of the local folklores are not properly documented, the move to transform local folklore into animation is indeed a good news. However, whether the transformation of the folklore into animation maintains its originality in terms of certain important elements, remain unknown. This matter can become an issue in the future, especially among the community in which the folklore belongs to. Therefore, the objective of this study is to analyze the original and the animated versions, in terms of theme, plot, main cast, setting, and values, particularly among the local folklores in the state of Sarawak (East of Malaysia). This study uses qualitative descriptive method in order to examine the folklores. Three animated folklores from Sarawak namely ‘Apai Saloi Hunting’, ‘The Legend of Santubong’ and ‘Commander of Mount Sadok’ were used as prime sources of the study. Data were also collected from people’s statement, written documents, historical heritage, and information from the internet. The results of the study revealed that all the three folklores have at least 95% of similarity between the original version and the animated version. The present study also provides information about the impact and contribution of animated folklore toward the society. It is hoped that more local folklores will be transformed into animated version by maintaining its originality, so that the intangible cultural heritage is being preserved and protected. Keywords: Folklore, Transformation, Animation, Impact